Analysis of the Effect of Road Alignment on Visibility Delay for Curved Roads - Hiroshi Kuniyuki; Seiya Tanaka; Fumitaka Fukuzawa; Masashi Makita (International Journal of Automotive Engineering)
This study analyzed the effects of road alignment on visibility delay for curves with experiments using a driving simulator. The results showed that the visibility behavior for curves was the first recognition of the existence of the curve, followed by the recognition of the curvature of the curve. Furthermore, it was found that the curve visibility delay in those phases was influenced by the left-right difference and the difference in curvature. In particular, there is a tendency for drivers to be late in noticing sharp left turns. It would be useful to warn the driver of the existence of a sharp curve at least 150 m before the curve and to encourage the driver to decelerate to prevent accidents. In addition, a left curve with an additional left lane can improve curve recognition, and expanding the shoulder or other space on the left side of the lane would be advantageous for curve recognition.